2004
DOI: 10.1210/en.2003-1274
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor (IGF)-I/IGF-Binding Protein-3 Complex: Therapeutic Efficacy and Mechanism of Protection against Type 1 Diabetes

Abstract: IGF-I regulates islet beta-cell growth, survival, and metabolism and protects against type 1 diabetes (T1D). However, the therapeutic efficacy of free IGF-I may be limited by its biological half-life in vivo. We investigated whether prolongation of its half-life as an IGF-I/IGF binding protein (IGFBP)-3 complex affords increased protection against T1D and whether this occurs by influencing T cell function and/or islet beta-cell growth and survival. Administration of IGF-I either alone or as an IGF-I/IGFBP-3 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 62 publications
0
56
0
Order By: Relevance
“…Since the mechanisms behind the HLA-conferred genetic susceptibility to T1D are poorly defined (36), we could speculate that the reduced IGF1 concentrations in subjects with the high-risk HLA genotype could explain, at least partially, the HLA-related risk for T1D, given that high IGF1 concentrations protect against the development of T1D (4,5,7,10,11,12). However, Fourlanos et al (35) recently proposed that an increased BMI simply promotes the development of T1D in subjects carrying lower-risk HLA risk genotypes by increasing the penetrance of lower-risk HLA genes, thus increasing the proportion of lower-risk HLA genes among subjects with higher BMI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the mechanisms behind the HLA-conferred genetic susceptibility to T1D are poorly defined (36), we could speculate that the reduced IGF1 concentrations in subjects with the high-risk HLA genotype could explain, at least partially, the HLA-related risk for T1D, given that high IGF1 concentrations protect against the development of T1D (4,5,7,10,11,12). However, Fourlanos et al (35) recently proposed that an increased BMI simply promotes the development of T1D in subjects carrying lower-risk HLA risk genotypes by increasing the penetrance of lower-risk HLA genes, thus increasing the proportion of lower-risk HLA genes among subjects with higher BMI.…”
Section: Discussionmentioning
confidence: 99%
“…The role of circulating IGF1 in paracrine and autocrine regulation has not been fully understood. However, it has been shown that treatment with IGF1 protects islets against cytokinemediated inhibition of insulin secretion and cell death by apoptosis (10), implying an important role of circulating IGF1 in the survival of pancreatic islets. There have also been studies demonstrating that the administration of IGF1 into the systemic circulation reduces the severity of insulitis and delays the onset of diabetes in non-obese diabetic mice (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…This observation was unexpected since remission is characterized by a rather less aggressive progression whereas elevated CCL3 has been shown to be associated with increased insulitis [23]. In addition, protection from immune-mediated diabetes in animal models was associated with decreased CCL3 concentrations [26]. Whether elevated CCL3 concentrations in remitters reflect an enforced leukocyte attraction due to the presence of more insulin producing β-cells remains speculative.…”
Section: Discussionmentioning
confidence: 99%
“…Severity of insulitis was performed as previously described (30). Insulitis index (I) was calculated as previously described (49).…”
Section: Assessment Of Diabetes and Insulitismentioning
confidence: 99%